Hambatan Pelaksanaan Praktikum Ipa Fisika Yang Dihadapi Guru SMP Negeri Di Kota Pekanbaru - Yennita '; Mugi Sukmawati; Zulirfan ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
A survey has been done on 46 teachers who taught Physics in grade VII and VIIIon 12 junior high schools within Pekanbaru. The respondents were selected from the schools thathad already have science laboratories. This survey was aimed to know the intensity and somedifficulties faced by the teachers in doing lab works while teaching science, especially Physics.The data of this research was collected by using questionnaires, and analyzed descriptively. Theresult of the research showed that the implementation of experiments while learning Physicswere rarely done by teachers. It was identified that there were some things causing teachersreluctant to do the experiments in the laboratory, according to the teachers’ perception. Someconstraints were include: 1. The intensity of teachers in joining laboratory workshops was stilllow, 2. The availability of the laboratory equipment was still not enough, 3. The material ofscience in high schools was very tight, therefore teachers were forced to give lecture than havingexperiments in the laboratory, 4. The learning objectives were quite difficult to be achievedthrough lab works, 5. Doing experiment was needed much time in preparation, 6. The time ofdoing experiment in each meeting always not enough, 7. The teachers’ knowledge on using thelaboratory equipment was still low, 8. The teachers faced difficulties in designing their ownworksheets, 9. Having no laboratory assistant to help teachers to do Physics experiments.